2007
DOI: 10.1016/j.devcel.2007.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinases Control Septin Phosphorylation in Candida albicans Hyphal Development

Abstract: Cyclin-dependent kinases (Cdks) control cytoskeleton polarization in yeast morphogenesis. However, the target and mechanism remain unclear. Here, we show that the Candida albicans Cdk Cdc28, through temporally controlled association with two cyclins Ccn1 and Hgc1, rapidly establishes and persistently maintains phosphorylation of the septin cytoskeleton protein Cdc11 for hyphal development. Upon hyphal induction, Cdc28-Ccn1 binds to septin complexes and phosphorylates Cdc11 on Ser394, a nonconsensus Cdk target.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 43 publications
4
133
0
16
Order By: Relevance
“…Scgin4D mutants exhibit similar defects, which are rather milder because of the existence of redundant kinases (Altman and Kellogg, 1997;Barral et al, 1999). We have previously shown that CaGin4 phosphorylates Cdc11 to prime it for further phosphorylation by Cdc28 during hyphal growth (Sinha et al, 2007). These observations indicate that Gin4 plays a conserved role in septin regulation.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Scgin4D mutants exhibit similar defects, which are rather milder because of the existence of redundant kinases (Altman and Kellogg, 1997;Barral et al, 1999). We have previously shown that CaGin4 phosphorylates Cdc11 to prime it for further phosphorylation by Cdc28 during hyphal growth (Sinha et al, 2007). These observations indicate that Gin4 plays a conserved role in septin regulation.…”
Section: Introductionmentioning
confidence: 59%
“…Mass spectrometry of immunopurified GFP-Gin4 detected phosphorylation in three perfect (T397, S455 and S467) and four minimal CDK sites (S477, S556, S1217 and T778) among dozens S469, S473, S477 KSMVSDES*S*AS*DDVFDKI S1077, S1078, S1080 RASHIS*VS*RPT*S*FQYKS S407, S409, T412, S413 KSMVS*DES*S*AS*DDVFDKI S1073, S1076, S1077, S1079 KNDYDDT*FVS*NSDEVHKR T1055, S1058 RGNNSSGHDDS*VPPPPPAHKV S1153 KST*KS*S*IDELANGTSTSGHRK T1094, S1096, S1097 KNDADPNNS*EQELVDEGIKQ S719 KNDYDDTFVS*NSDEVHKRQ S1058 RQPSIS*S*S*IMS*QSNHNHPQKI S10, S11, S12, S15 KLLET*SCGSPHYAAPEIVSGLKY T191 RALS*EGNHASEELTLEDVENLKR S745 KSELQDEET*EKNGDGLPYGIERE T69 KLPDGKS*T*KS*S*IDELANGT*STSGHRK S1093, T1094, S1096, S1097, T1105 KYPMSNEDLIS*EKS*LPHPQTGYKS S300, S303 KTIENNTNAATNTTTQQQLPS*PAESKE S1217 RDYELPEPTVEDSNLT*DDYMTEIRK T875 RERDYELPEPT*VEDSNLTDDYMTEIRK T868 KAGLAEPEYET*ET*DGEDKVS*VIDLDDHLADRR T989, T991, S998 RYMIDEPNQPQLQQPALSQVPENPIVDES*PDLMQSAKI S555 { Phosphorylation site mapping by tandem mass spectrometry was carried out as described previously (Sinha et al, 2007). *Asterisks indicate phosphoserine or phosphothreonine residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong genetic evidence that Cln1p and Cln2p in particular are needed to promote proper septin ring assembly (Benton et al 1993;Cvrckova et al 1995;Gladfelter et al 2005) and that some septins are direct CDK targets (Tang and Reed 2002;Egelhofer et al 2008), although phosphosite mutants of individual septins did not have any obvious effect on septin ring assembly. In contrast to the inconclusive findings from S. cerevisiae, analogous work in the related Candida albicans provided strong evidence that CDK-mediated septin phosphorylation directly impacts septin organization and hyphal growth (Sinha et al 2007;Gonzalez-Novo et al 2008). Thus, it seems highly likely that CDKs directly regulate septin assembly as well as indirectly promote septin organization through Cdc42p polarization.…”
Section: Polarity Establishment In G1mentioning
confidence: 82%
“…Ccn1p-Cdc28p has been shown to phosphorylate Cdc11p at residue 394 (Sinha et al, 2007). This phosphorylation is dependent on prior phosphorylation at position 395 by the Gin4p kinase.…”
Section: Control Of Vesicle Trafficmentioning
confidence: 99%